A Seventeenth-Century Confraternity in Santa Ana, San Salvador. What It Can Tell Us about That Era - MacLeod, Murdo J. (Confraternitas)

(untitled) (Iter Press, 2020)
The colonial settlement of Santa Ana has been somewhat neglected by authorities and historians. This article looks at the founding there in 1672–73 of a confraternity dedicated to Saint Rose of Lima and how this illustrates several aspects of life at that time. When the bishop of Guatemala imposed full Tridentine authority on Santa Ana, many confraternities tried to avoid it. Quiet struggles over the roles of the local priest, supervision of the elections of office holders, the location of the new altar, ethnic and gender memberships, and the changing nature of the multiethnic settlement, all led to readjustments. These contentions continued throughout the colonial period and after.